Cost-benefit analysis potential in feeding behavior of a predatory snail by integration of hunger, taste, and pain - Gillette, Rhanor (The National Academy of Sciences, 2000)
Hunger/satiation state interacts with appetitive and noxious stimuli to determine feeding and avoidance responses. In the predatory marine snail Pleurobranchaea californica, food chemostimuli induced proboscis extension and biting at concentration thresholds that varied directly with satiation state. However, food stimuli also tended to elicit avoidance behavior (withdrawal and avoidance turns) at concentration thresholds that were relatively low and fixed. When the feeding threshold for active feeding (proboscis extension with biting) was exceeded, ongoing avoidance and locomotion were interrupted and suppressed. Noxious chemostimuli usually stimulated avoidance, but, in animals with lower feeding thresholds for food stimuli, they often elicited feeding behavior. Thus, sensory pathways mediating appetitive and noxious stimuli may have dual access to neural networks of feeding and avoidance behavior, but their final effects are regulated by satiation state. These observations suggest that a simple cost-benefit computation regulates behavioral switching in the animal's foraging behavior, where food stimuli above or below the incentive level for feeding tend to induce feeding or avoidance, respectively. This decision mechanism can weigh the animal's need for nutrients against the potential risk from other predators and the cost of relative energy outlay in an attack on prey. Stimulation of orienting and attack by low-level noxious stimuli in the hungriest animals may reflect risk-taking that can enhance prey capture success. A simple, hedonically structured neural network model captures this computation.